Singularity According to Personalized Education in Digital Era - Paola Perochena González; Gisela Matilde Coria; José Fernando Calderero Hernández (Pontificia Universidad Católica del Perú, 2017)
Singularity, opening and autonomy are essential elements considered fundamental in «Personalized Education». The article delves into the consequences of the singularity of every day practice of teaching and learning in the current context characterized, among other features, by increasing digitization. In the light of the outcome, it follows that the unique and unreapetable being of the person must be considered in relation to the teaching and educational reality from planning, execution and assessment. Every training process has to adapt to each specific situation and the features and interests of the student encouraging his/her research capacity and creativity. The teacher adopts, among others, a role of trainee and assessment becomes a source of learning, improving in this way the quality of academic training.